Morphological evaluation of a regurgitant orifice by 3-D echocardiography: applications in the quantification of valvular regurgitation - Smith, Barry K.; Kolda, Michal; Anayiotos, Andreas (My University, 1999)
The clinical evaluation of blood flow regurgitation through a heart valve or stenotic lesion is an unresolved problem. The proximal flowfield region has been the study focus in the last few years; however, investigators have failed to identify an accurate and reliable calculation scheme due to lack of geometric information about the shape and size of the regurgitating or stenotic orifice. Presented here is a superior method of calculation, by using three-dimensional (3-D) echocardiography combined with Doppler velocimetry. The geometric structure of the orifice in a regurgitating porcine prosthetic valve in vitro was formulated by 3-D image construction of sequentially obtained 2-D images. The velocity flowfield was accessed by color Doppler flow mapping (CD) and continuous-wave Doppler (CW). Two accurate methods of calculation of regurgitant variables were developed. The first method calculated peak regurgitant flow rate from CD and the second method calculated regurgitant flow volume from CW. Both methods showed excellent correlation with the corresponding true values from an electromagnetic flowmeter. The promising preliminary results in such a realistic porcine model indicate the possibility of establishing a routine procedure to be tested in the clinical setting. The clinical evaluation of blood flow regurgitation through a heart valve or stenotic lesion is an unresolved problem. The proximal flowfield region has been the study focus in the last few years; however, investigators have failed to identify an accurate and reliable calculation scheme due to lack of geometric information about the shape and size of the regurgitating or stenotic orifice. Presented here is a superior method of calculation, by using three-dimensional (3-D) echocardiography combined with Doppler velocimetry. The geometric structure of the orifice in a regurgitating porcine prosthetic valve in vitro was formulated by 3-D image construction of sequentially obtained 2-D images. The velocity flowfield was accessed by color Doppler flow mapping (CD) and continuous-wave Doppler (CW). Two accurate methods of calculation of regurgitant variables were developed. The first method calculated peak regurgitant flow rate from CD and the second method calculated regurgitant flow volume from CW. Both methods showed excellent correlation with the corresponding true values from an electromagnetic flowmeter. The promising preliminary results in such a realistic porcine model indicate the possibility of establishing a routine procedure to be tested in the clinical setting.
Keywords: Echocardiography; Doppler ultrasonography; Hemodynamics; Cardiovascular system